Unveiling the full picture of malnutrition in Sub-Saharan Africa: The extended composite index of anthropometric failure among children under-5 in the SDG era - Amare Muche; Aznamariam Ayres; Tilahun Dessie Alene; Robel Asaminew Mekonnen; Elsabeth Addisu; Gebeyehu Tsega; Yawkal Tsega (PLoS ONE, 2025)
Introduction The burden of malnutrition among children under-5 in Sub-Saharan Africa (SSA) remains a significant public health concern. Traditional indices such as stunting, wasting, and underweight often failing to capture the overlapping and multifaceted nature of malnutrition. The Extended Composite Index of Anthropometric Failure (ECIAF) offers a comprehensive measure by integrating stunting, wasting, underweight and obese/overweight addressing the overlap and co-occurrence of different forms of malnutrition conditions, thus providing a more accurate depiction of nutritional deficiencies. Aligning with the Sustainable Development Goals, the ECIAF serves as a robust tool for health policymakers and public health practitioners to identify high-risk populations, allocate resources effectively, and improve health outcomes for young children in this region. This study aimed to determine the pooled prevalence of the Extended Composite Index of Anthropometric Failure and to identify its associated factors among children under-5 in SSA countries. Methods This study is a secondary data analysis of nationally representative community-based cross-sectional Demographic and Health Surveys (DHS) conducted in Sub-Saharan African countries, including a weighted sample of 176,141 children under-5 years. The recent demographic and health survey of 26 Sub-Saharan African countries were involved in this analysis. A multilevel binary logistic regression model was fitted to identify factors associated with ECIAF in children under-5 years old. The AOR with its 95% CI was estimated, and a level of significance of 0.05 was used to determine the significant factors of ECIAF. Results The pooled prevalence of ECIAF among children under-5 was 36% (95% CI: 33%, 40%) in Sub-Saharan Africa. Key factors associated with increased odds of ECIAF included: increasing child age (6–23 months [AOR = 1.56; 95% CI: 1.46, 1.66] & 24–59 months [AOR = 2.03; 95% CI: 1.88–2.19]), multiple births [AOR = 2.38; 95% CI: 2.05–2.76], reducing birth size (average [AOR = 1.20; 95% CI: 1.14, 1.26] & small [AOR = 1.80; 95% CI: 1.68–1.93]), having comorbidity [AOR = 1.12; 95% CI: 1.07, 1.16], reducing level of mother’s educational status (primary [AOR = 1.20; 95% CI: 1.12, 1.28] & no formal education [AOR = 1.36; 95% CI: 1.27, 1.45]), increasing number of children under-5 in the household (2 children [AOR = 1.17; 95% CI: 1.10, 1.23] & 3–5 children [AOR = 1.14; 95% CI: 1.06, 1.22]), reducing household wealth status (rich [AOR = 1.28; 95% CI: 1.17, 1.41], middle [AOR = 1.31; 95% CI: 1.19, 1.44], poor [AOR = 1.42; 95% CI: 1.28, 1.56] & poorest [AOR = 1.45; 95% CI: 1.31, 1.61]), living in rural area [AOR = 1.15; 95% CI: 1.09, 1.22]. Protective factors included female sex [AOR = 0.69; 95% CI: 0.66–0.72], birth interval >24 months [AOR = 0.86; 95% CI: 0.81, 0.91] health facility delivery [AOR = 0.79; 95% CI: 0.74–0.83], and antenatal care attendance [AOR = 0.83; 95% CI: 0.77–0.90]. Conclusions The pooled prevalence of ECIAF in children under-5 was high in Sub-Saharan Africa. Addressing this burden requires scaling up nutrition-sensitive interventions that tackle underlying determinants of child malnutrition, including poverty reduction, women’s education and empowerment, improved access to quality health services, safe water, sanitation, and hygiene programs. Such multisectoral strategies, alongside maternal and child health interventions, are essential to mitigate the identified risk factors and sustainably reduce ECIAF in the region.